Serum high-mobility group box 1 is correlated with interferon-α and may predict disease activity in patients with systemic lupus erythematosus. (August 2019) - Tanaka, A; Ito, T; Kibata, K; Inagaki-Katashiba, N; Amuro, H; Nishizawa, T; Son, Y; Ozaki, Y; Nomura, S
Sensing self-nucleic acids through toll-like receptors in plasmacytoid dendritic cells (pDCs), and the dysregulated type I IFN production, represent pathogenic events in the development of the autoimmune responses in systemic lupus erythematosus (SLE). Production of high-mobility group box-1 protein (HMGB1) promotes type I IFN response in pDCs. To better understand the active pathogenic mechanism of SLE, we measured serum levels of HMGB1, thrombomodulin, and cytokines (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-13, IL-17A, IL-17F, IFNα, IFNγ, TNFα) in 35 patients with SLE. Serum HMGB1 and IFNα were significantly higher in patients with active SLE (SLE Disease Activity Index (SLEDAI) score ≥ 6) compared with healthy donors or patients with inactive SLE. Furthermore, the HMGB1 levels were significantly correlated with IFNα levels. By qualitative analysis, the detection of serum IFNα or HMGB1 suggests active SLE and the presence of SLE-related arthritis, fever, and urinary abnormality out of SLEDAI manifestations. Collectively, HMGB1 and IFNα levels are biomarkers reflecting disease activity, and qualitative analysis of IFNα or HMGB1 is a useful screening test to estimate SLE severity and manifestations. Our results suggest the clinical significance of type I IFNs and HMGB1 as key molecules promoting the autoimmune process in SLE.